ABOUT THE PRINCIPLE OF LAWFULNESS IN THE ACTIVITY OF PUBLIC ADMINISTRATION. CONSTITUTIONAL ASPECTS - Oana ŞARAMET (Valahia University Law Study, 2018)
In any state of law, by the provisions of the fundamental law, fundamental constitutional principles are identified, principles which emphasize the theoretical concept of the state of law. Along with aspects as the separation of powers within a state, representative governance, independence of justice, the acknowledgement and protection of the citizen’s fundamental rights and freedoms, the state of law also considers the principle of legality. Legality must pertain to all state dimensions and not just in regard to the organization of justice, the solution to litigation, identifying certain deeds as crimes, the criminal sanction which is to be applied to a certain deed. Thus, lawfulness must pertain to executive power, public administration in regard to its structure and organization, but also in regard to the activity of multiple and various structures of public administration. The existence and enforcement of this principle in public administration, as well as in regard to its activity, can be aspects considered by express regulation or not, as found in constitutional regulations. However, regardless of law the constitutional lawmaker of a state perceived the necessity of regulating the principle of lawfulness in the fundamental law, whether express or not, of general character or applied to one or more authorities which exercise one of the three powers of the state, as they are identified based on the principle of the separation of powers and the equilibrium of powers within a state, the existence of this principle and the basis of any action of the public authority, namely one of the public administrations based on this principle is, in our opinion, unquestionable.
Keywords: principle; lawfulness; public administration; constitution; regulation